Assessment of Oxidative Stress by the Estimation of Lipid Peroxidation Marker Malondialdehyde (MDA) in Patients with Chronic Periodontitis: A Systematic Review and Meta-Analysis - Khadijah Mohideen; Krithika Chandrasekar; Saranya Ramsridhar; Chandini Rajkumar; Snehashish Ghosh; Safal Dhungel (Hindawi Limited, 2023)
Objective. The present systematic review and meta-analysis aimed to assess the oxidative stress-mediated lipid peroxidation end product malondialdehyde (MDA) in periodontitis using the available literature. Materials and Methods. An electronic literature search was performed for the published articles from 2000 to 2022 in PubMed (MeSH), Science Direct, Wiley Online library, and cross-reference using specific keywords. Results. The literature search identified 1,166 articles. After analyzing the abstracts of the obtained articles, the articles were excluded for the following reasons: duplicate studies (n = 395) and not relevant to the research question (n = 726). The remaining 45 articles were chosen for full-text evaluation. Finally, the present qualitative synthesis selected 34 articles that met the inclusion criteria for evaluation and removed the articles which did not meet the required criteria (n = 11). Out of these, 16 articles had coherent data for quantitative synthesis. The meta-analysis used the standardized mean differences method at a 95% confidence interval by random-effects model. The periodontitis group displayed significantly higher MDA levels (P<0.001) in gingival crevicular fluid, saliva, and serum samples of the studies analyzed than the healthy control. Conclusion. The analyzed studies showed significantly higher MDA levels in various biological samples of patients with periodontitis, supporting the role of elevated oxidative stress and consequent lipid peroxidation in periodontitis.